Structuring variation in romance linguistics and beyond in honour of Leonardo M. Savoia / edited by Mirko Grimaldi, University of Salento ; Rosangela Lai, University of Florence ; Ludovico Franco, Nova University of Lisbon ; Benedetta Baldi, University of Florence. - Grimaldi, Mirko; Lai, Rosangela; Franco, Ludovico; Baldi, Benedetta; Savoia, Leonardo Maria, 1948- (Linguistik Aktuell / Linguistics Today ;, 2018)
Current theoretical approaches to language devote great attention to macro- and micro-variation and show an ever-increasing interest in minority languages. In this respect, few empirical domains are as rich and lively as the Italo-Romance languages, which together with Albanian were the main research domain of Leonardo M. Savoia. The volume covers areas as different as phonology, morphology, syntax and the lexicon. A broad range of Romance languages is considered, as well as Albanian, Greek and Hungarian, shedding new light on many classical topics. The first section focuses on morphosyntax, both in the narrow sense and with regard to its interfaces. The second section focuses on clitics and pronouns. The third section deals with a number of issues in phonology and syntax-phonology interface. The last section turns the reader's attention beyond formal linguistics itself and examines variation in the light of neurosciences, pathology, historical linguistics and political discourse.